2018
DOI: 10.1186/s12906-018-2371-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of Lactobacillus reuteri V3401 on biomarkers of inflammation, cardiovascular risk and liver steatosis in obese adults with metabolic syndrome: a randomized clinical trial (PROSIR)

Abstract: BackgroundObesity is characterized by increased fat mass and is associated with the development of insulin resistance syndrome (IRS), usually known as metabolic syndrome. The alteration of the intestinal microbiota composition has a role in the development of IRS associated with obesity, and probiotics, which are live microorganisms that confer a health benefit to the host, contribute to restore intestinal microbiota homeostasis and lower peripheral tissue insulin resistance. We aim to evaluate the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…We performed a randomized, double-blind, crossover, placebo-controlled, single-center trial in patients with a new diagnosis of MetS, according to the criteria of the International Diabetes Federation (IDF). The complete study design including sample size, randomization, and the trial protocol have been previously published [17] and registered at as NCT02972567. The study was conducted in agreement with the Standard Protocol Items: Recommendations for Interventional Trials (SPIRIT) guidelines.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed a randomized, double-blind, crossover, placebo-controlled, single-center trial in patients with a new diagnosis of MetS, according to the criteria of the International Diabetes Federation (IDF). The complete study design including sample size, randomization, and the trial protocol have been previously published [17] and registered at as NCT02972567. The study was conducted in agreement with the Standard Protocol Items: Recommendations for Interventional Trials (SPIRIT) guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…Sample size was calculated based on the range and median value of lipopolysaccharide (LPS) and assuming a power of 80% and a significant level of 5% [17]. In brief, a total of 53 out of 60 adult patients were recruited at the Endocrinology and Nutrition Clinical Management Unit, University Hospital of Jaén (Jaén, Spain) by qualified personnel.…”
Section: Methodsmentioning
confidence: 99%
“…Tenorio-Jimenez et al [ 30 ] report that the 12-week administration of a daily dose of 5 × 10 9 cfu L. reuteri V3401 in capsules was associated with lower levels of inflammation biomarkers, such as TNF-α, IL-6, IL-8 and soluble intercellular adhesion molecule-1 (sICAM-1), in obese adults aged 18 to 65 years with metabolic syndrome, as well as with a reduced risk of CVD. Szulinska et al [ 31 ] also observed that supplementation with the multispecies probiotic Ecologic ® Barrier modified both the functional and biochemical parameters of vascular dysfunction in a group of 81 obese postmenopausal Caucasian women.…”
Section: Probioticsmentioning
confidence: 99%
“…Hence this study will provide valuable scientific information about the effects of this strain in IRS and metabolic syndrome patients. 51…”
Section: Role Of Probioticsmentioning
confidence: 99%